Emergence of Colistin Resistance in Carbapenem-Resistant Hypervirulent Klebsiella pneumoniae Under the Pressure of Tigecycline - Zhang, Yawei; Wang, Xiaojuan; Wang, Shifu; Sun, Shijun; Li, Henan; Chen, Hongbin; Wang, Qi; Wang, Hui (Frontiers in Microbiology, 2021)
Colistin and tigecycline are the last options against carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP). Intersecting resistance determinants have been detected between these antibiotics; however, there is only limited evidence of such association. Here, we describe a colistin-resistant CR-hvKP isolated from a patient with severe neonatal bacteremia treated with tigecycline as opposed to colistin before isolation of this strain, providing a clinical clue to colistin resistance under tigecycline pressure. Furthermore, an ST11-K64 KPC-2–producing, colistin-susceptible CR-hvKP strain was subjected to experimental evolution toward colistin resistance under tigecycline and colistin pressure to verify this phenomenon in vitro. The biological impact of acquiring colistin resistance on fitness and virulence was also studied. As expected, the parental strain rapidly developed colistin resistance under both tigecycline and colistin selection. However, different from the colistin resistance mechanism in the clinical strain that was due to an ISKpn26 insertion in the mgrB gene, the mutants in this study developed colistin resistance through a 4.4 or 4.6 kb deletion including the mgrB locus as well as the kdgR, yobH, yebO, yobF, cspC, ftsI, and rlmA genes. Although the virulence of the colistin-resistant mutants, as determined in the Galleria mellonella model, decreased compared with that of the parent strain, it was still higher than that of NTUH-K2044. This suggests a slight virulence cost when CR-hvKP develops colistin resistance under tigecycline or colistin pressure. Together, our results provide clinical and experimental evidence for the association between colistin resistance and tigecycline pressure in CR-hvKP, highlighting a critical issue in the clinical setting.